The orchestra : an introduction to the world of classical music - Blackwoood, Alan, 1932- (Brookfield, Conn. : Millbrook Press, 1993)
Traces the history of the orchestra and discusses the musical instruments that make up the various orchestral families.
"A First guide."
"A Quarto book"--T.p. verso.
Includes index.
Keywords: Orchestra -- Juvenile literature; Musical instruments -- Juvenile literature; Orchestra; Musical instruments